Penyembunyian Data Rahasia pada Citra Digital Berbasis Chaos dan Discrete Cosine Transform - Prabowo, Anton; Hidayatno, Achmad; Christyono, Yuli (Departemen Teknik Elektro, Universitas Diponegoro, 2011)
Steganography is one of technique that developed to keep the security of data by hidding or embedding it in other data media so that it’s content or even it’s existence is not notice. Many steganography methode have been developed in the last few years, but it still needed a steganography system with highest capacity and robustness. By combining and modifying few technic, in this Final Project has made a steganography system that used to embedding and extracting secret data in image data form (BMP 8 bit grayscale and 24 bit color), voice data form (WAV PCM 11.025 KHz 8 bit mono), and text data form (TXT) into cover data in image data form (BMP 8 bit grayscale). Data hidding was done at frequency domain by applying DCT (Discrete Cosine Transform) and chaos theory was applied using logistic map equation. Program was made using Borland Delphi 7 programming language. By using subjectif quality, RMS (Root Mean Square) metrics, and similarity ratio measurement parameter, program performance was observed by doing research consist of: research of initialitation parameter change influences; research of embedding and extracting secret digital data in image, voice, and text form into cover digital data in image form; research of program realibility from data manipulation operation including brigthness modification, contrast modification, resizing, cropping, and JPEG compression. Keyword : steganography, discrete cosine transform, chaos theory, logistic map, root mean square.